Burden of meningitis and encephalitis in Iran from 1990 to 2021: findings from the Global Burden of Disease study - Pegah Rasoulian; Emadoddin Kazemi; Tina Taherkhani; Hoda Niavarani; Nikaein Zabeti Targhi; Zahra Farrokhi; Aida sajedi; Amirhossein Memari; Khashayar Danandeh (BMC Neurology)
Abstract Background Meningitis and encephalitis are significant contributors to morbidity and mortality worldwide. This study aimed to provide a comprehensive overview of the trends and epidemiology of these diseases in Iran from 1990 to 2021. Methods Data from the Global Burden of Disease (GBD) study were utilized to assess the epidemiology and burden of meningitis and encephalitis in Iran. This study compared these findings with those of global and Middle East and North Africa (MENA) countries. Age-standardized rates for incidence, prevalence, and disability-adjusted life years (DALYs) were calculated, and trends over time were analyzed. Results This study revealed a substantial reduction in the burden of meningitis over the observed period, with a -85.81% decrease in age-standardized DALYs rates from 1990 to 2021. Encephalitis rates also decreased, though to a lesser extent. Significant disparities in disease burden were observed across different sexes and age groups, with higher rates among males and in the < 5 years and ≥ 90 years’ age groups. Provincial disparities were also noted, with the highest age-standardized DALYs rates for meningitis in provinces such as Sistan and Baluchistan, Kohgiluyeh and Boyer-Ahmad, and Hamadan. Conclusion This study highlights the progress made in reducing the burden of meningitis and encephalitis in Iran over the past three decades. However, the observed disparities across sexes, age groups, and provinces emphasize the need for continued efforts in surveillance, prevention, and treatment to further alleviate the impact of these diseases.